An evaluation of the species and subspecies of the genus Salmonella with whole genome sequence data: Proposal of type strains and epithets for novel S. enterica subspecies VII, VIII, IX, X and XI - Pearce, ME; Langridge, GC; Lauer, AC; Grant, K; Maiden, MCJ; Chattaway, MA (Elsevier, 2021)
Species and subspecies within the Salmonella genus have been defined for public health purposes by biochemical properties; however, reference laboratories have increasingly adopted sequence-based, and especially whole genome sequence (WGS), methods for surveillance and routine identification. This leads to potential disparities in subspecies definitions, routine typing, and the ability to detect novel subspecies. A large-scale analysis of WGS data from the routine sequencing of clinical isolates was employed to define and characterise Salmonella subspecies population structure, demonstrating that the Salmonella species and subspecies were genetically distinct, including those previously identified through phylogenetic approaches, namely: S. enterica subspecies londinensis (VII), subspecies brasiliensis (VIII), subspecies hibernicus (IX), and subspecies essexiensis (X). The analysis also identified an additional novel subspecies, reptilium (XI). Further, these analyses indicated that S. enterica subspecies IIIa isolates were divergent from the other S. enterica subspecies, which clustered together and, on the basis of ANI analysis, subspecies IIIa was sufficiently distinct to be classified as a separate species, S. arizonae. Multiple phylogenetic and statistical approaches generated congruent results, suggesting that the proposed species and subspecies structure was sufficiently biologically robust for routine application. Biochemical analyses demonstrated that not all subspecies were distinguishable by these means and that biochemical approaches did not capture the genomic diversity of the genus. We recommend the adoption of standardised genomic definitions of species and subspecies and a genome sequence-based approach to routine typing for the identification and definition of novel subspecies.